Effectiveness of 'Mother Supportive Group' intervention on childhood nutrition improvement in Monaragala District of Sri Lanka - Nimal Gamagedara; Eresha Mendis; Nihal Wijesinghe (College of Community Physicians of Sri Lanka, 2020)
Introduction: Effective, largescale, and nutrition-sensitive interventions addressing underlying determinants are required to accelerate progress in under-five nutrition.   Objectives: To determine the effective coverage of Mother Supportive Group (MSG) intervention among its primary target population and its effectiveness in promotion of nutrition and growth of under-five children   Methods: A descriptive, cross-sectional study was carried out among under-five children of Monaragala District. The study population was categorized into 'MSG' if the child was registered with intervention and into 'Non- MSG' if it was not. MSGs were defined as effective, if MSG meetings were held once a month consecutively over the past six months with a meeting report for each meeting held. A sample of 1140 children (570 from each 'MSG' and 'Non-MSG' groups) was selected by systematic random sampling method. Weight and height of children were measured with appropriate instruments. Other information was collected by an interviewer administered questionnaire.   Results: Effective coverage of primary target population by MSG intervention was 2.6% and it was not uniformly implemented in the community. Only one medical officer of health (MOH) area reported effective coverage of 25%, while it was 10-15% in five MOH areas and less than 1% in two MOH areas. Attending Growth Monitoring and Promotion Programme in more than the recommended frequency was significantly higher (77.5%) in MSG (Non-MSG=49.7%). Fathers' smoking was significantly high (54%) in MSGs (Non-MSG=46%). Feeding on solid food during illness has significantly improved with MSG intervention (MSG=20.7% versus Non-MSG=11.9%). None of the other practices and selected behaviours showed significant improvement with MSGs. No significant difference in the prevalence of underweight, stunting and wasting was detected between MSG and Non-MSG groups.   Conclusions: Effective coverage of MSG intervention was significantly low while its implementation was not uniform in the community. MSG intervention was not effective enough at its present level of implementation, to show significant nutrition and growth promotion among children of the under-five category. It is recommended to revisit the MSG intervention before further implementation.